Gamification, a possible alternative using the liveworksheets.com platform - Messias, Júlio Brando; Messias, Inalda Maria de Oliveira; Araújo , Rosane Jamille de Oliveira; Florêncio, Mônica Simões; da Silva Filho, João Ferreira; Luz, Betty Rose de Araújo; da Silva, Silvana de Fatima Ferreira (Seven Editora, 2023)
The planning of didactic activities should guide the pedagogical strategies for a quality education, which significantly assists the teaching-learning process, and in this context, an alternative to the learning processes are the educational games and the playful inserted in the educational scenario is a process capable of motivating the pedagogical action. Liveworksheets.com is a platform that allows you to transform traditional printable sheets (pdf, jpg, png) into interactive exercises with self-correction, called "interactive spreadsheets". The objective of this work is to present the versatility of the educational platform – Liveworksheets.com, directed to the elaboration of games, such as word hunting and crossword puzzles. The analysis was based on the spreadsheets available on the platform itself, being exploratory research of bibliographic character. The platform allows you to develop word hunting and crossword puzzle games without major difficulties. In the end it was possible to verify that the platform besides being dynamic and interactive can provide opportunities for changes in the way of teaching and learning, making it possible to transform fun into learning.DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-157